Publiczna pomoc dla polskich placówek medycznych - Węgrzyn, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
For a few years already we have been searching in Poland for rational method of collecting and distributing financial sources that enables fulfilling the health care system public obligations. As a result of failures in budgeting systems and of the lack in internal reorganization systems , the level of crediting in health care system is higher and higher. One of the methods that enables changes in the system is a restructuring and public support law. Its conditions scope, and effects so far are presented in this text. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 421-430